The perception of families about the guide “every time is time for caring”: DOI: 10.15343/0104-7809.2010213642 - Lislaine Aparecida Fracolli; Anna Maria Chiesa (O Mundo da Saúde, 2010)
The project “Our Children: Windows of opportunities” is a health promotion strategy conceived to support the participation of families in stimulating child development. The project elaborated the Guide “Every time is time for caring”. The Guide was an instrument of education in health that described actions to be carried through by families for stimulating children development. The aim of this study was to evaluate the use of the Guide by families. Subjects were 34 families enrolled in a Basic Health Unit of the city of São Paulo. Data collection was done with a semi-open questionnaire. Results show that the Guide was very used by families. 72.4% of the families had the Guide and 81% talked about the content of the Guide with health professionals from the Family Health team, mainly with the Communitarian Health Representative. We concluded the Guide is an adequate instrument for education in health, because it allowed a dialogue on children development between families and health professionals.